Muscle-to-bone crosstalk: the Wnt/β-catenin pathway is a candidate mechanism mediating the signalling between C2C12 muscle cells and 2T3 osteoblasts - Magarò, Maria Sara; Bertacchini, Jessika; Potì, Francesco; Checchi, Marta; Benincasa, Marta; Sena, Paola; Palumbo, Carla (Italian Journal of Anatomy and Embryology, 2018)
Bone and muscle have been recognized as endocrine organs since they produce and secrete “hor- mone like factors”, osteokines and myokines, that can mutually influence each other and other tis- sues, giving rise to “bone-muscle crosstalk” [1]. Recently, evidences emerged that myokines have pro- found effects on osteocytes in culture and vice versa [2][3]. Besides, skeletal muscle secreted factors have been found to promote osteocytes and osteoblasts viability through activation of the Wnt/β- catenin pathway [2]. To determine whether myokines can potentially regulate osteogenesis, we condi- tioned the differentiation of 2T3 osteoblasts with 25% medium from early (day 1), mid (day 7) or late (day 14) myotubes. Osteoblast conditioned differentiation was investigated from different viewpoints: i) analysis of mRNA and protein levels of marker genes of differentiation; ii) characterization of the functional maturation by studying the deposition of mineralized matrix and the activity of alkaline phosphatase enzyme. To date, we have demonstrated that the early conditioned medium (day 1, CM 1) decreased significantly the mineralization degree of osteoblasts compared to control. Besides, CM 1 induced statistically significant increase in the expression of Sclerostin, both SOST mRNA transcrip- tion and protein synthesis during osteoblast differentiation. Sclerostin is a secreted glycoprotein main- ly expressed in bone and cartilage matrix, considered a negative regulator of bone growth due to its role as an antagonist of the Wnt/β-catenin pathway. It has also been found to inhibit the pre-osteo- cyte differentiation of osteoblasts in vitro [4]. These data prompted us to analyze the protein content of CM1 and surprisingly we found that myotubes at day 1 and 4 of differentiation secrete Sclerostin. Therefore, we hypothesize that muscle cell-secreted Sclerostin may act as an endocrine negative reg- ulator of 2T3 differentiation through inhibition of Wnt/β-catenin signaling and such effect may be enhanced by the induced osteoblast isoform acting in an autocrine loop. Further experiments are needed to test the involvement of Sclerostin as mediator of the effects of the early CM. Thus, we are planning the following experiments: i) 2T3 differentiation with recombi- nant Sclerostin combined with its antibody-mediated neutralization, ii) overexpression of Sclerostin in 2T3 cells, iii) treatment of C2C12 cells with SOST siRNA and 2T3 conditioned differentiation with C2C12 siRNA-treated CM.